Evaluation of admixture effect on strength and durability properties of concrete - a critical review - V, Mahesh; Chemalapati, Hemalatha; A, Vani; Dandagala, Sreenivasulu (International Journal of Engineering and Technology, 2018)
The present paper is focused on the study of admixture effect on strength and durability properties of concrete. In this study selected admixtures bentonite clay, coconut shell, cow dung ash, crushed rubber, egg shell, glass powder, groundnut shells, rich husk, stone dust, sugar bagasse etc., research papers has been reviewed. Inspite of several usage of waste, presently millions of tons are produced every year and remain unused all around the world and causes serious environment problems. Utilization of waste products all over the world has become challenging task for civil engineers. High costs of cements are not economical for all the types of construction works. Therefore, it is necessary to utilize the locally available materials for improving the properties of concrete in the field of construction industry. The usage of different waste material for the improvement of concrete properties has drawn much attention to the researchers. Moreover, several researchers were made an investigation on laboratory tests on partial and fully replacement of cement, sand, aggregate in concrete and various properties like workability, compressive strength, and density are studied. Based on the research work carried out several researchers we can conclude that the utilization of different usage of waste material as resources and prevents environmental pollution. It is also observed that waste materials can be used as an alternate material for the better improvement of strength and durability properties of concrete.